Rancang Bangun Sistem Deteksi Dini Ketinggian Air Banjir Berbasis IoT dengan Sensor Ultrasonik - Rushendra Rushendra; Mohamad Yusuf; Rahmad Hidayat; Yakob Liklikwatil; Dimas Surya Subrata (STMIK IKMI Cirebon, 2019)
Flooding is a phenomenon of natural events that often occur and are faced in almost all countries in the world, including Indonesia. Losses derived from this flood can be minimized if the community gets a warning about the potential for flooding in an area. However, with the absence of automatic flood water level detection and the slow dissemination of information, it is often that people are only aware of floods after this natural disaster occurs. In this study, experimental research methods are used to correctly test hypotheses regarding causal relationships. For this purpose, an internet-based flood of a detection system based on IoT was designed with an HC-SR04 ultrasonic sensor. From the test data, the speed of internet access affects the success of sending data to the webserver. A better speed can send data successfully constantly. Meanwhile, if the speed is worse, the success of sending data will decrease. If the data is not sent successfully, the system will pass the data and proceed to the next data. That way the data that appears and monitored on the android application does not experience delays and is always the latest data.